A case of Madura foot - Khandhedia, Parth; Desai, Shashank (International Surgery Journal, 2022)
Madura foot is a chronic infection caused by bacteria actinomycetes or by fungi eumycetes and is endemic in tropical and subtropical areas. The cases have been reported from the other areas as well. Foot is the primary involved organ. A 50-year-old male presented with multiple small swellings over right foot who was already diagnosed as Madura foot for which the patient was on the medications from several years with no effect. The infection tends to recur after the medications were stopped. He took penicillin injections till it was banned few years ago without any benefit. He visited the surgical outpatient department (OPD) and managed by below knee amputation from tibial tuberosity preserving 15 cm of proximal leg as stump. There was no complication post-operatively and patient was discharged in a stable condition with clean wound. The diagnostic and therapeutic challenges along with the epidemiological data emphasize the need of raising the awareness of physicians to this devastating condition.